Can Cryptocurrency, Gold and Bonds Play a Role as a Safe Haven for the Indonesian Capital Market? - Hartono, Paulus; Robiyanto, Robiyanto (Jurnal Ekonomi Kuantitatif Terapan, 2021)
The purpose of this research to test the cryptocurrency, gold and bonds as safe haven assets to Indonesian capital market. The data used in this study is the daily closing data of cryptocurrency, gold (GOLDIDR) and the Indonesian Government Bond Index (IGBI) during the period on August 2015 to December 2018 obtained from Investing, Yahoo Finance, and Spindices. The analysis of the data is used Ordinary Least Square (OLS) and Quantile Regression (QREG). The results found that ethereum can be a safe haven. While bitcoin, ripple, gold, and the Indonesian Government Bond Index (IGBI) cannot be a safe haven for the Indonesian capital market.